On the Philosophical Definition of Human Play Using the Tools of Qualitative Content Analysis. Issue 1 (2nd January 2021) - Lebed, Felix
ABSTRACT: Formulating a metaphysical definition of human play faces three main difficulties. First, for many years the very possibility, or need, for such a definition has been questioned. Second, very often attempts to metaphysically understand play 'slide off' to one of two incompatible poles: comprehension of play as a mental stance or mode of action vs. its interpretation as real action and a type of cultural activity. Third, metaphysical views of play have not yet decided through which main philosophical category it is possible to combine these polar points of view into a single whole. This article is based on the definiteness of human play in principle. It is dedicated to the philosophical categorization of play using the tools of qualitative content analysis and encompasses the widely cited views of leading scholars. The use of this methodology allowed me to distinguish between nine main philosophical themes through which play can be differentiated from all other forms of human existence. They are: 'partial escape from routine reality', 'freedom', 'autotelicity', 'play as a kind of being', 'imagination', 'exaggeration', 'temporality', 'discovery' and 'relocation'. Through an in-depth study of these themes by reviewing current philosophical discussions about play it was possible: (1) to strengthen Fink's (1960a, b) thesis of play as a kind of existing and to focus comprehension of human play on the notion of 'escape to another being' as the desired 'single whole' joining play as state and play as action (this thesis is part of the main focus of the proposed study); and (2) to clarify and add to the themes found in the course of the research and formulate an overall philosophic definition of human play.